La danza folclórica como estrategia metodológica y su aplicación para fomentar la práctica de valores culturales, en los estudiantes del quinto grado de la escuela de Educación Básica Dr. Víctor Emilio Uzcátegui, en el periodo académico 2018 - 2019. Lineamientos Alternativos . - Armijos Ramon, Flor Elizabeth (2019)
The present investigation Folkloric dance as a methodological strategy and its application to promote the practice of cultural values, in the students of the fifth grade of the Escuela de Educación Básica Dr. Víctor Emilio Uzcátegui, in the academic period 2018-2019. Alternative Guideline, had as a general objective: Analyze folk dance as a methodological strategy and its application to promote the practice of cultural values, in the students of the fifth grade of the Escuela de Educación Básica Dr. Víctor Emilio Uzcátegui, in the academic period 2018-2019; the type of study was descriptive that is framed by a mixed approach, that is to say, quali-quantitative and a quasi-experimental design; The methods considered were the scientific, analytic-synthetic, descriptive, inductive-deductive and statistical; The interview, survey and observation techniques were used as techniques, supported by instruments such as: the question guide, the questionnaire and the checklist; and, the procedures performed were related to the theoretical-diagnostic foundation and the design of the alternative guidelines. As a result, it was found that the teacher does not use folk dance as a didactic resource in the teaching of historical and cultural content, so that students have a low knowledge about culture and the importance it has in society. The research participants were a teacher and 27 students of the fifth grade of the school of Basic Education "Dr. Víctor E. Uzcátegui. " It is concluded that folk dance can be used as a didactic resource in the teaching of cultural issues in the area of social studies, in addition, it is important that the school include in its projects the cultural mainstreaming in order to promote respect for the diverse cultures, improve coexistence and create good habits.